2005
DOI: 10.1002/jso.20391
|View full text |Cite
|
Sign up to set email alerts
|

The trans‐metastasis hepatectomy (through metastases previously ablated with radiofrequency): Results of a 13‐case study of colorectal cancer

Abstract: TMPRFH is a new and safe technique, combining RF ablation and trans-RF-hepatectomy, which makes it possible to propose a curative approach in certain patients with non-resectable bilateral LMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
(22 reference statements)
0
13
0
1
Order By: Relevance
“…Their safety and efficacy have already been proven (16,18) and the location of LM is no longer a limit to RFA. Fourth, due to the high number of RF ablations in the remaining part of the liver, maximum sparing of normal parenchyma is critical :…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their safety and efficacy have already been proven (16,18) and the location of LM is no longer a limit to RFA. Fourth, due to the high number of RF ablations in the remaining part of the liver, maximum sparing of normal parenchyma is critical :…”
Section: Discussionmentioning
confidence: 99%
“…The surgeon constantly referred to drawing indicating the sites and sizes of LM produced following ultrasound detection before RFA. Simple RFA sessions were performed (14), but when necessary, the central bile ducts were also cooled to protect them from heat (a technique we described in 2001) (15,16), or a trans-RF hepatectomy was performed after RF destruction of one or several LM located along a suitable transection line, in order to spare as much normal parenchyma as possible (a technique we described in 2002) (17,18). Patients underwent a postoperative CTscan before being discharged from hospital.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…Ouellet et al [37] reported no radiological evidence of disease at 6 months in four patients subjected to TMH. Elias et al [39] reported no local recurrence in 13 patients with bilateral unresectable CRC LM treated with TMH with hepatic inflow occlusion, after a mean follow-up of 19.4 months.…”
Section: Discussion Radiofrequency Ablation (Rfa)mentioning
confidence: 98%
“…RFA can artificially increase the surgical margin thus allowing TMH [23,[37][38][39]. The technique is applicable to tumors close to a vessel or bile duct when the resection margin is less than 10 mm and in patients with bilateral LM when the only possible future hepatectomy plane passes through a LM.…”
Section: Discussion Radiofrequency Ablation (Rfa)mentioning
confidence: 99%
“…These results are to be balanced with the 20% 5-year survival rates obtained using chemotherapy alone in patients with unresectable CLM [5] . In such a context, it therefore appears that combined strategies mixing ablative procedures [84] and adjuvant intra-arterial chemotherapy [8] as well as repeated resection in case of recurrence could help prolong survival [85][86][87][88] .…”
Section: Long-term Outcomementioning
confidence: 99%